Comparative analysis of phytochemical and antioxidant activities of the Nishatipal decoction and it’s freeze dried powder - Randima, K.A.D.K.; Perera, P.K.; Arawwawala, L.D.A.M. (Faculty of Indigenous Medicine, University of Colombo, 2020)
Nishatipal decoction is a traditional polyherbal formulation which is used extensively by Sri Lankan Ayurvedic and Traditional medical practitioners to treat Diabetes Mellitus. Eight different medicinal plants are present in this decoction. The aim of the present study was to establish phytochemical, chromatographic analysis of the decoction and its freeze-dried powder. In addition, in-vitro antioxidant activity was evaluated for the freeze-dried powder of Nishatipal decoction. Phytochemical screening of the decoction and its freeze-dried powder exhibited many primary and secondary metabolites. Organoleptic properties indicated, the decoction was a dark brown liquid with a characteristic odor, bitter taste and sticky on touch. pH and density of the decoction were 5.22 and 1.009075g/cm3 at 27oC. Furthermore, peaks at similar Rf values for both decoction and freeze-dried powder indicated the presence of similar bioactive compounds. In-vitro antioxidant activity revealed that total polyphenolic content and DPPH radical scavenging activity were in significant levels in freeze dried form of Nishatipal decoction. The findings from this study provided evidence that the decoction contains medicinally important bioactive compounds which help amelioration of Diabetes Mellitus. In addition, quality control parameters were established for Nishatipal decoction and its freeze-dried form for the first time.
Keywords: Antioxidants; Nishatipal; Phytochemicals; TLC; HPTLC